Optical sensing of analytes in aqueous solutions with a multiple surface-plasmon-polariton-wave platform - Swiontek, Stephen E. (Nature Publishing Group, 2013)
The commonly used optical sensor based on surface plasmon-polariton wave phenomenon can sense just one chemical, because only one SPP wave can be guided by the interface of a metal and a dielectric material contained in the sensor. Multiple analytes could be detected and/or the sensing reliability for a single analyte could be enhanced, if multiple SPP-wave modes could be excited on a single metal/dielectric interface. For that to happen, the partnering dielectric material must be periodically non-homogeneous. Using a chiral sculptured thin film (CSTF) as that material in a SPP-wave platform, we show that the angular locations of multiple SPP-wave modes shift when the void regions of the CSTF are infiltrated with a fluid. The sensitivities realized in the proof-of-concept experiments are comparable to state-of-research values.